Cost Savings of Reduced Constipation Rates Attributed to Increased Dietary Fibre Intakes in Europe: A Decision-Analytic Model - Jordana K. Schmier,; Vanessa Perez,; Susan Cloran,; Carolyn Hulme-Lowe ,; Kathryn O’Sullivan, (Journal of Pharmacy and Nutrition Sciences, 2015)
Mounting evidence shows that functional constipation contributes to increased healthcare utilization, impairment in quality of life, and lost work productivity. Among those with functional constipation, relatively small dietary changes may alleviate symptoms and result in considerable constipation-related healthcare cost savings. The study objective was to estimate the economic impact of increased dietary fibre consumption on direct medical costs associated with constipation from a payer perspective. A decision-analytic spreadsheet model was created to perform the analysis. Literature searches identified sources for input parameters, including prevalence of functional constipation, dietary fibre intakes, proportion of the population meeting recommended intakes, and the percentage that would be expected to benefit from increased dietary fibre consumption. The model assumes that 25% of adults make no change in fibre intake, 25% increase intake by 3 g/day, 15% increase intake by 4 g/day, 25% increase intake by 5 g/day, and 10% increase intake by 11 g/day. A dose-response analysis of published data was conducted to estimate the percent reduction in constipation prevalence per 1 g/day increase in dietary fibre intake. Annual direct medical costs for constipation were derived from the literature and updated to 2014. Sensitivity analyses explored robustness of the model. Under base case assumptions, annual cost savings were estimated at ?127,037,383 in the United Kingdom, €8,791,992 / ?7,244,513 in Ireland, and €121,699,804 in Spain. Increasing dietary fibre consumption is associated with considerable cost savings, with these estimates being conservative given the exclusion of lost productivity costs in the model.